Zmartwychwstanie Chrystusa w nauce Kościoła prawosławnego - Mirosław Białous (Wrocławski Przegląd Teologiczny)
This article argues that in the thinking of the Orthodox Church, in spite of the simplified preconceptions, the kerygma of the resurrection is not limited to preach the theology of glory, but it covers the entire paschal mystery: the Cross of Christ, His descent into hell, His victory over death and the entrance to the glory of the Father. Such a way of seeing is a result of the biblical and patristic teachings. Its great importance lies in the fact that it takes into account the unity of the mystery of Jesus Christ, God and man. Therefore it assume the intrinsic unity of the cross and the incarnation, the passion and the glory. This unity is strongly present in the Orthodox theology but also the Liturgy celebrated in the Lent, Easter or Sunday.